Two new species of the genus Caryanda StDl (Orthoptera: Acrididae) from Yunnan, China - Mao, Ben-Yong; Ren, Guo-Dong; Ou, Xiao-Hong (Zootaxa, 2007)
Caryanda aurata sp. nov. and Caryanda albomaculata sp. nov. are described from Yunnan, China. Type specimens are deposited in the College of Life Sciences and Chemistry, Dali University (CLDU), Yunnan Province, China.